AVALIAÇÃO DA EFICÁCIA DA LIMPEZA E DESINFECÇÃO TERMINAL DE COLCHÕES HOSPITALARES - Monia Alves Mendes de Souza (2022)
ABSTRACT Healthcare-related infections have raised concern in the healthcare environment as a potential reservoir of microorganisms and the spread of pathogenic organisms. The mattress is a source of horizontal transmission among other surfaces and other patients, patient companions, and professionals, requiring attention to the cleaning process and sanitizing them to reduce the maximum possible pathogenic agents of infections related to health care. The objective was to evaluate the effectiveness of cleaning and terminal disinfection of hospital mattresses. This was a cross-sectional, analytical, and quantitative study, based on primary data on the materials and evaluation of the effectiveness of the cleaning and disinfection process of mattresses in the surgical and medical clinic units of a teaching hospital in a capital of Midwest Brazil throughout the years 2021 and 2022. Data collection took place from the application of an instrument with questions about the terminal cleaning and disinfection process and the evaluation of 32 mattresses before and after this process. Two methods were used to evaluate the effectiveness of cleaning and disinfection: fluorescent marker at six points and colony-forming unit (CFU) count at three points, both in three sites of each mattress (upper, middle, and lower). When considering the number of CFU found in mattresses and compared to two groups of up to 199 CFU and more than 200 CFU, there were significant changes in their decrease (upper part: p=0.001; middle: p<0.001; and lower part: p<0.001 ), however, regarding the microbiological analysis, considering the reference value for approval with <60 CFU or <2.5 CFU/cm2 or <2.5 CFU/cm2 in cultures, 100% (n=32) were disapproved after the cleaning and disinfection process. Concerning the fluorescent marker, 93.8%/30 mattresses were non-compliant, indicating a significant failure in the cleaning process. Also, it was found that, among the sample of 100% (n=32) of mattresses, there was no statistical association among their sites, before and after cleaning and disinfection by CFU analysis (p=0.340-0.582); likewise, there were no statistical differences in the analysis with the fluorescent marker in any of the sites of the mattresses (p=0.304). The results of the association of fluorescent and microbiological marker (UFC) tests did not show a statistical association in any of the sites of the mattress, both before and after cleaning and disinfection (chi-square test, p-value ranging from 0.341 to 0.982). Although there was a decrease in CFU after cleaning and disinfecting the mattresses, additional compliance criteria described in the literature were not achieved, and no association between the methods was found. Therefore, mattress cleaning and disinfection monitoring methods were implemented as objective parameters to measure the rigor of compliance with terminal cleaning of mattresses. On the other hand, there is a need to review the mattress terminal cleaning protocol and carry out compliance inspections, encourage collaboration between infection prevention and control teams and the environmental cleaning service, encourage accountability, and inspire educational interventions with the environmental cleaning team. Descriptors: Beds. Infections. Disinfection. Nursing Audit. Equipment Contamination.